ELLUL’S THESIS ON THE MOBILIZING ROLE OF POLITICAL PERSUASION THROUGH THE PERSPECTIVE OF NEURAL BASIS OF MOTIVATED REASONING - Komad, Marina (Politeia, 2025)
The thesis of Jacques Ellul—that successful political persuasion is focused primarily on influencing behavior rather than attitudes—is examined in this work from the perspective of neuroscience and the findings of a neuroscientific experiment conducted by Drew Westen. Specifically, by exploring the neural basis of the cognitive process known as motivated reasoning, Westen arrived at results indicating the dominant role of emotions in political decision-making and judgment under the influence of such reasoning. Based on these findings, Westen concludes that the political brain is, in fact, an „emotional brain” and that changes in political attitudes are not driven by new information, but rather by new emotions. This paper investigates how such a conclusion either confirms or redefines Ellul’s thesis—namely, that in the persuasive sequence following the dissemination of political messages, behavioral change precedes, and only potentially leads to, attitude change, which, in the context of successful political persuasion, may or may not occur. In a broader context, the paper uses this case to raise the question of the application of neuroscience in the field of political marketing, with the aim of empirically testing traditional claims in political persuasion theory—claims that are often based, to varying degrees, on speculation. The study also offers guidelines for future research, proposing that the application of neuroscientific methods may provide insight into the sequencing of persuasive processes and the role of emotion and motivated reasoning within that sequence.